Modeling the Distribution of Household Bank Deposits in Bulgaria - Peshev, Petar (Research Papers, 2020)
Using Bulgarian National Bank’s data on households’ bank deposits facilitates the creation of econometric models for the study of inequality in their distribution. Calculation of the Gini coefficient by household’s bank deposits data serves to create a dependent variable for modeling financial inequality. The financial inequality in the country over the period 2005-2017 is determined by the changes in a number of macroeconomic variables that may have different impacts in the short and long term.
Keywords: Financial wealth; Inequality in distribution of deposits; Gini coefficient of households’ bank deposits